2019
DOI: 10.21037/ajo.2019.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the quality & quantity of otorhinolaryngology research in Australia: 1989–2018

Abstract: Background: Trends in the quality and quantity of surgical research in Australia have recently experienced considerable growth, stemming from the adoption of the "evidence-based practise" framework. The aim of this 30-year retrospective epidemiological study is to identify and analyse trends in publication of clinical otorhinolaryngology research in Australia from 1989 to 2018. Methods: The 24 highest ranked otorhinolaryngology journals worldwide were identified based on their respective impact factor (IF). Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Bibliometrics is the process of analyzing the content and citations of journal articles to quantify trends in publication type, topic area, institutions of origin and dissemination of published data [ 4 ]. In OHNS, previous bibliometric studies indicate a considerable increase in the quantity and quality of research in the international arena [ 5 , 6 ]. However, within the Canadian landscape, Gurberg et al, demonstrated a decrease in Canadian authored papers in Otolaryngology journals over a 4-year period from 2008 to 2012 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics is the process of analyzing the content and citations of journal articles to quantify trends in publication type, topic area, institutions of origin and dissemination of published data [ 4 ]. In OHNS, previous bibliometric studies indicate a considerable increase in the quantity and quality of research in the international arena [ 5 , 6 ]. However, within the Canadian landscape, Gurberg et al, demonstrated a decrease in Canadian authored papers in Otolaryngology journals over a 4-year period from 2008 to 2012 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wasserman et al, (15) in their study of 2,584 papers published between 1993 and 2003, found small but significant improvement in average LOE over that time interval. A more recent review from Australia in 2019 found that the total number of publications increased along with an increase in the proportion of high-level evidence with exponential increases in both the quantity and quality of the evidence over a 30 years period (16).…”
Section: Discussionmentioning
confidence: 99%
“…By most metrics including LOE, these efforts appear to be working 2 . Even in smaller fields such as Otolaryngology, progress is being made demonstrating improvement in the quality of research output over the last several decades 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…2 Even in smaller fields such as Otolaryngology, progress is being made demonstrating improvement in the quality of research output over the last several decades. [3][4][5][6][7] There are several potential explanations for the observed increase in quality, but essentially distill down to two factors-authors submitting higher quality work and/or journals seeking/selecting higher quality work. Both are likely true.…”
mentioning
confidence: 99%